Information literacy in the South Eastern European region: the way forward - Špiranec, Sonja; Banek Zorica, Mihaela (2010)
A diagnosis of the state of information literacy in the SEE region, based on earlier research and insights (Proposal for an IL Platform and an Action Plan for Central and South-East European Countries, UNESCO “Training the Trainers in Information Literacy” Workshop, Ankara) gives the overall impression that the majority of countries in this part of Europe is lagging behind information literacy achievements. Due to the impact of information literacy on the development of knowledge-based societies and economies, the lack of clearly stated information literacy agendas deepens social and economical disparities and divides between this region and other parts of Europe. The authors of this paper believe that the obstacles to information literacy in the countries across the region are more or less the same and that this similarities are caused by the fact that information literacy is a highly contextual phenomenon, determined by different sociotechnical, political or historical factors. On the other hand, all those countries are experiencing changes and transformations that provide opportunities to increase awareness of the vital importance of information literacy. In the paper the authors will analyze the variables that have determined the poor state of information literacy in the region, point out concrete opportunities that emerge from contextual factors experienced by all those countries (e.g. educational reforms, the Bologna Agreement) and discuss further steps that need to be done in order to achieve some advancement in this field.
Projekt MZOS
ENG